2018
DOI: 10.1515/hmbci-2018-0055
|View full text |Cite
|
Sign up to set email alerts
|

Copper and zinc in stage I multiple myeloma: relation with ceruloplasmin, lipid peroxidation, and superoxide dismutase activity

Abstract: Background The main aim of this study was to assess the serum levels of copper (Cu), zinc (Zn) with lipid peroxidation, Cu/Zn superoxide dismutase (Cu/Zn SOD) activity, and ceruloplasmin (Cp) in multiple myeloma (MM) patients. Materials and methods The study was conducted in 34 MM patients at stage I. Serum Cu and Zn levels were measured by atomic absorption spectrometry. Also, spectrophotometric assays of malondialdehyde (MDA) levels in addition to Cp and Cu/Zn SOD were quantitated. Results The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…[10] The results showed that the level of copper and zinc was significantly increased in patients with MM when compared with healthy control while the results of magnesium and calcium of MM patients were slightly decreased in comparison with healthy control, this result agrees with the results of study conducted by Khadem Ansari et al (2019). [11]…”
Section: Discussionmentioning
confidence: 99%
“…[10] The results showed that the level of copper and zinc was significantly increased in patients with MM when compared with healthy control while the results of magnesium and calcium of MM patients were slightly decreased in comparison with healthy control, this result agrees with the results of study conducted by Khadem Ansari et al (2019). [11]…”
Section: Discussionmentioning
confidence: 99%
“…Excess Cu may lead to cancer occurrence. Its carcinogenic mechanism may be related to copper zinc superoxide dismutase (Cu/Zn SOD) activating dioxygen and ceruloplasmin to scavenge free radicals by affecting the process of iron metabolism [42,43]. Many types of cancer are characterized by increased intratumoral copper and/or altered systemic copper distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in 1975, Schwartz highlighted the potential role of copper as a carcinogenic and diagnostic/prognostic marker ( 69 ). Meanwhile, studies found elevated copper serum concentrations in various tumors ( 28 ), such as stage I multiple myeloma ( 29 ), reticulocyte sarcoma, bronchial and laryngeal squamous cell carcinoma, lung cancer ( 31 ), leukaemia, lymphoma ( 70 ), cervical cancer, breast cancer and gastric cancer ( 71 , 72 ). In addition to elevated serum copper levels, elevated copper concentrations were reported in the nails and/or hair of patients with tumors, such as breast, prostate and cervical cancers ( 73 ).…”
Section: The Relationship Between Copper and Tumorsmentioning
confidence: 99%
“…With scientific advances, the abnormal accumulation of copper in cancer cells was found to be an important feature in differentiating them from normal cells. Relevant experimental data showed that several cancer cells maintained trace elements, such as zinc, selenium or iron, at normal levels, but copper levels were significantly elevated ( 28 ), such as in stage I multiple myeloma ( 29 ), lung cancer ( 30 ) and acute lymphoblastic leukaemia ( 31 ).…”
Section: Introductionmentioning
confidence: 99%